Time of last meal and its association with indices of metabolic health in young Indian adults (Indian Journal of Public Health Research & Development, 2026)
Background:Chrono-nutrition explores the role of meal timing, frequency, and regularity in shaping metabolic health through circadian mechanisms. Evidence indicates that glucose metabolism, insulin secretion, and appetite regulation follow circadian rhythms and are influenced by the temporal distribution of energy intake. Late or evening-skewed eating patterns and circadian misalignment, common in modern lifestyles, are associated with poorer metabolic outcomes. This study examined the association between meal timing, percent body fat, blood glucose, and insulin levels in adolescents and young adults (16-25 years old).Methods: Of 1,313 apparently adolescents and young adults screened, complete data were available for 1,015 participants after applying predefined exclusion criteria. Body composition was assessed using bioelectrical impedance, while fasting and 2-hour post-glucose blood samples were analysed for plasma glucose, insulin, and HbA1c using standard methods. Meal timing was recorded based on the last meal consumed the previous night, and data were analysed using SPSS 27 with p
Keywords: fasting, meal frequency, meal timing, obesity, cardiovascular health, diabetes